Propuesta de un manual de funciones, valuación de puestos por puntos y un reglamento de admisión y empleo para el talento humano de la empresa Golden Valley, planta s.a. del cantón Portovelo, provincia de El Oro - Tandazo Yaguana, Danny Gabriel (2015)
This research project's main objective is to develop a proposal of manual functions, job evaluation points and regulations for admission and employment to enable effective management in the company Golden Valley, Plant SA. Its development was based on the theoretical framework - scientist, besides the use of investigative methods like: Deductive to gather information; Inductive Analysis of the current situation of the company and Analytical for the interpretation of data obtained through research techniques: direct observation, interview and survey manager 18 employees and 187 employees of the company Golden Valley, Plant SA, Portovelo canton province of El Oro. Analyzed and processed data from a proposal containing the Manual Job Classification, Regulation of Admission and Employment prepared in accordance with company policies, the same as to be considered by the entity are raised, will enable the normal development of talent human. The procedure followed for the development of this project are summarized as follows: first, to understand the development of the workforce in the company we applied an interview with the General Manager and a survey of members of the administrative staff and workers working in the plant; With the results obtained and interpreted proceeded to the development of Post Classification Manual, the same identification consisting of office, nature of work, class characteristics and minimum requirements for each job; Valuation of positions was performed in the company determining factors and degrees to be evaluated with their weightings. Weights for each grade according to the job title was established. Tabulated data, the slope formula and equation of the straight line to graph the salaries are below the established ranges and implement the adjustment of wages and salaries in the mining company Golden Valley Floor SA was applied also develop the Regulation of Admission and Employment. Finished the proposal came to the conclusion that human talent working in the company does not have an instructive for the description and analysis of each job, so know the main functions of the position and the requirements that this requires. The recruitment is not done according to established policies, causing recruited staff often does not have the capabilities to carry cargo. They have no clear definition of the hierarchical levels, causing confusion and evasion of responsibility. Personnel management becomes inefficient due to the lack of posts Classification Manual containing the prerequisites that must have the candidates to fill vacant positions. It is essential to the execution of a devaluation on points system, which ensures fair and equitable compensation of employees and workers of the company, according to their capabilities and performance within each field